A statistical quality control study on Kimberly-Clark Philippines, Inc. - Balanggao, Dedrick P.; Guan Hing, Dianne Mae S.; Maghuyop, Lourdes D. (Diliman, Quezon City College of Engineering, 2005)
Kimberly Clark Philippines, Inc. (KCPI) is one of the manufacturing facilities of the multinational company Kimberly and Clark Company. KCPI embarked its operations in January 1964 when Kimberly Clark Corporation acquired the controlling interest of Hygienic Products, Incorporated. It began with its facility situated at Barrio Calumpang, Marikina producing feminine napkins and facial tissues. Today, the KCPI facility is located in San Pedro, Laguna where it manufactures products for personal care and hygiene and exports to its South East Asian affiliates in Malaysia, Thailand and Singapore. It is the maker of well-known brands of facial and bathroom tissue such as KLEENEX, SCOTT, ACE and JOY, disposable diaper of KIMBIES and HUGGIES brand and feminine care products like KOTEX and NEWTEX. In this study, the group confined their efforts in the analysis of KCPI's present sampling plan based on the true capability of the process. Specifically, the group verified whether the sample size they are using for each attribute and variable is sufficient to detect the true variability of the process. The group focused on the sanitary pad line in the JOA3 machine which produces all grades or variants of sanitary pads. Only two grades were evaluated, Pad 1 and Pad 2, since they undergo practically the same production process with negligible variations. The data used in this study span three months starting from mid-May to mid-August of 2004. For each grade, all attributes and six variables namely pad weight, pad thickness and four seal strengths, named seal strength 1, 2, 3 and 4 were analyzed. Upon application of Statistical Process Control techniques on each quality characteristic, the trial court charts showed points outside the control limits signaling the presence of assignable causes. To proceed with process capability analysis these assignable causes were identified and the new control limits for the in-control process were obtained. The group however was not able to make a thorough investigation on the intermittent variations as the management could not provide the necessary information regarding assignable causes due to confidentiality. The group was instead given an overview of the causes of variation in the process that the management established from their previous analyses. The management attributes most variability to the machine itself that were caused by equipment modifications in the attempt to achieve the same level of production of newer and top of the line machines. In their attempt to speed up production, the consequences was an increase in variability that they just consider as inherent to the machine. In the Process Capability Analysis, capability and variability of the original data as well as the revised data of each quality characteristic were obtained and compared. Results show that process capability increased with the revision and a significant decrease in variability was realized. In the Acceptance Planning, the sample sizes required to detect the true variability of the process based on the process capability were obtained and compared with the current sample sizes used. Based on the results, the required sample size for the attributes of Pads 1 and 2 are higher than the present and the group recommends increasing the sample sizes to at least 17 and 34, respectively. For the rest of the quality characteristics, the sample sizes are small compared to the existing sample sizes used in the sampling plan. Therefore, the current sampling method is more powerful to detect process shifts, and may be retained. However, the group strongly recommends reducing the sample sizes to minimize the costs generated as inspection is destructive. For future studies, KCPI may consider a Methods Engineering evaluation of the Feminine Care Mill which is currently set up in a large structure that formerly served as a warehouse. The Mill at present is at a tolerable state but an improvement of the facility layout and the overall working condition would bring immense benefits to the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Kimberly Clark Philippines Incorporated; Paper industry; Quality control